Legal Resolution of Discriminative Acts for Persons with Disabilities as Human Rights Violations in Indonesia - Pakpahan, Zainal Abidin (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Discrimination against people with impairments constitutes a global violation of human rights. This study employs a normative law approach. Discrimination against people with disabilities is punishable by imprisonment for up to one year and/or a fine of up to one hundred million rupiah under Articles 15 and 16 of Law of the Republic of Indonesia Number 40 of 2008 on the Elimination of Discrimination, Race, and Ethnicity if it includes ethnicity, religion, race, and culture, as well as discrimination against children and women with disabilities. As a result, Articles 144 and 145 of Law of the Republic of Indonesia Number 8 of 2016 Concerning Persons with Disabilities expressly offer criminal punishments for discrimination. As a result, addressing acts of discrimination against people with disabilities is a small violation of human rights if it arises because of the victim's material and moral damages. The process can be carried out in a non-adjudication manner through a mediation process, as well as a settlement process using the adjudication route through prosecution to the District Court in the event of material and moral losses experienced by the victim, indicating the need for a fair legal solution for perpetrators of acts of discrimination against people with disabilities as a minor human rights violation in Indonesia.